2021
DOI: 10.3393/ac.2021.00913.0130
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Pelvic Lymph Node Dissection After Neoadjuvant Chemoradiotherapy in Patients With Rectal Cancer: A Single-Center Experience and Literature Review

Abstract: Purpose: We aimed to evaluate the surgicopathological outcomes of lateral pelvic lymph node dissection (LPLD) and long-term oncological outcomes of selective LPLD after neoadjuvant chemoradiotherapy (nCRT) in patients with locally advanced rectal cancer and compare them to those of total mesorectal excision (TME) alone based on pretreatment magnetic resonance imaging (MRI).Methods: We compared the TME-alone group (2001–2009, n=102) with the TME with LPLD group (2011–2016, n=69), both groups having lateral lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Although the prognostic significance of lateral pelvic lymph node dissection (LPLND) is still controversial, recent data suggest that clinically positive lateral pelvic lymph nodes (LPLNs) might have a high risk of treatment failure irrespective of PCRT or LPLND [ 47 48 49 ]. LPLND is a technically demanding procedure owing to its technical difficulty, risk of incomplete dissection, and higher incidence of intraoperative bleeding and surgical morbidity including urinary and sexual dysfunction [ 48 ].…”
Section: Extended Techniques In Robotic Surgerymentioning
confidence: 99%
“…Although the prognostic significance of lateral pelvic lymph node dissection (LPLND) is still controversial, recent data suggest that clinically positive lateral pelvic lymph nodes (LPLNs) might have a high risk of treatment failure irrespective of PCRT or LPLND [ 47 48 49 ]. LPLND is a technically demanding procedure owing to its technical difficulty, risk of incomplete dissection, and higher incidence of intraoperative bleeding and surgical morbidity including urinary and sexual dysfunction [ 48 ].…”
Section: Extended Techniques In Robotic Surgerymentioning
confidence: 99%
“…Robotic colorectal surgery for locally invasive colorectal cancer offers technical advantages for complex surgeries such as combined resection for direct invasion to adjacent organs or extensive lymphadenectomy with optimal wrist movements, 3D visualization, and tremor stabilization, permitting adequate exposure and dissection in selected cases. Surgical radicality is important in the treatment of colorectal cancer, and recent studies showed robotic surgeries for extensive and complex procedures such as para-aortic or LPND or pelvic exenteration [43][44][45]. In contrast, the benefits of sphincter-preserving surgeries can be maximized when combined with robotic surgery, which enables more precise and selective surgeries such as intersphincteric resection, partial excision of the levator ani muscle for low-lying rectal cancer invading the ipsilateral levator ani muscle (Figure 6), and partial Denonvilliers' fascia excision (Figure 7) for anteriorly-located rectal cancer, especially in the setting of neoadjuvant chemoradiotherapy [1,2,46].…”
Section: Robotic Surgery For Extensive and Selective Proceduresmentioning
confidence: 99%
“…1,2 However, several recent reports have demonstrated that, even with CRT, omitting LLN dissection could result in recurrence in those cases with suspected LLN metastasis, and an increasing number of facilities are performing elective LLN dissection. [3][4][5][6] In Japan, the current guidelines recommend that surgeons perform TME with LLN dissection without preoperative treatment for advanced lower rectal cancer. 7 However, because of the complicated nature of the procedure, the risk of postoperative dysfunction, and complications such as dysuria, an increasing number of facilities omit LLN dissection in cases wherein LLN metastasis is not suspected on imaging.…”
mentioning
confidence: 99%
“…1,2 However, several recent reports have demonstrated that, even with CRT, omitting LLN dissection could result in recurrence in those cases with suspected LLN metastasis, and an increasing number of facilities are performing elective LLN dissection. 3–6…”
mentioning
confidence: 99%